Survival and dispersal in a newly-founded temperate Barnacle Goose Branta leucopsis population - van der Jeugd, Henk (Wildfowl, 2013)
Survival rates and dispersal were studied in a newly-founded temperate Barnacle Goose Branta leucopsis population in the Netherlands using marked individuals. BirdsÂ were ringed at three localities: two in the Delta area in the southwest of theÂ Netherlands and one in FryslÃ¢n in the north. Annual survival decreased duringÂ 2004â€“2012 from c. 95% to c. 75%, probably due to an increase in hunting pressureÂ introduced to reduce the size of the population and its damage to agricultural crops.Â A decrease in survival should lead to a decline in numbers in the population, but thisÂ was not apparent from the summer counts. Natal dispersal was high: 56% of malesÂ attempted to breed > 10 km from their natal site, and 38% at > 100 km from theirÂ natal area. In females, these figures were 30% and 24%, respectively. A substantialÂ number of male Barnacle Geese most probably emigrate to the large population thatÂ breeds along the shores of the Barents Sea, and the Dutch Barnacle GooseÂ population currently is a source, from which restocking of the Barentâ€™s SeaÂ population takes place. Breeding dispersal was low. Disturbance of colonies mayÂ influence dispersal as birds from one colony disturbed by foxes showed remarkablyÂ high natal and breeding dispersal.